Consumer Evaluation of Dual Focus Mutual Aid - Magura, Stephen (2008)
Double Trouble in Recovery (DTR) is a “dual focus,” 12 step-based mutual aid program tailored to assist recovery from co-occurring substance use and psychiatric disorders. OBJECTIVE: To determine consumers’ perceptions of DTR’s usefulness for their recoveries and the relationships between perceived DTR usefulness and self-help processes, self-efficacy to cope with problems in recovery, and changes in behaviors conducive to dual recovery. METHODS: Consumers attending DTR groups, located within a psychiatric day-treatment program, completed anonymous surveys 8 months (N=19) and 20 months (N=61) after DTR was implemented. RESULTS: DTR participants rated DTR favorably and length of DTR attendance was significantly associated with increased self-efficacy for recovery and positive changes in recovery-oriented behaviors. Perceived DTR usefulness was significantly associated with greater engagement in three specific self-help processes and increased self-efficacy for recovery; notably, these associations were independent of consumers’ overall satisfaction with the treatment program. CONCLUSION: This study is the first to document consumers’ perceived usefulness of DTR in relation to indicators of recovery. Overall, the study provides additional evidence for the benefits of implementing consumer-led dual focus groups in treatment programs.